2021
DOI: 10.21203/rs.3.rs-218770/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rising ecosystem water demand exacerbates the lengthening of tropical dry seasons

Abstract: The timing and length of the dry season is a key factor governing ecosystem productivity and the carbon cycle of the tropics. Mounting evidence has suggested a lengthening of the dry season with ongoing climate change. However, this conclusion is largely based on changes in precipitation (P) compared to its long-term average (P ̅) and lacks consideration of the simultaneous changes in ecosystem water demand (measured by potential evapotranspiration, Ep, or actual evapotranspiration, E). Using several long-term… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…and more severe dry seasons (Xu et al, 2022;Agudelo et al, 2019;Arias et al, 2015), with an increase in frequency of droughts, floods and fires (Barlow et al, 2020;Lovejoy and Nobre, 2018;Marengo and Espinoza, 2016); a recent study by (Gatti et al, 2021) has demonstrated how the southeastern edge of the Amazon rainforest has already reached the tipping point, acting as a net carbon source instead of a carbon sink. These findings agree with the projections showed in our results, which now are part of a long series of studies showing alarming signs of an incoming process of savannization in the area; the feedback loop created by a disruption in the carbon cycle such as the one showed by Gatti et al (2021) could further exacerbate the savannization process.…”
Section: Biome Shifts: Key Emerging Trendsmentioning
confidence: 99%
“…and more severe dry seasons (Xu et al, 2022;Agudelo et al, 2019;Arias et al, 2015), with an increase in frequency of droughts, floods and fires (Barlow et al, 2020;Lovejoy and Nobre, 2018;Marengo and Espinoza, 2016); a recent study by (Gatti et al, 2021) has demonstrated how the southeastern edge of the Amazon rainforest has already reached the tipping point, acting as a net carbon source instead of a carbon sink. These findings agree with the projections showed in our results, which now are part of a long series of studies showing alarming signs of an incoming process of savannization in the area; the feedback loop created by a disruption in the carbon cycle such as the one showed by Gatti et al (2021) could further exacerbate the savannization process.…”
Section: Biome Shifts: Key Emerging Trendsmentioning
confidence: 99%